Spontaneous light-emitting photosensitive resin composition, color conversion layer produced using the same, and display device
A self-luminous photosensitive resin composition with quantum dots and specific additives forms a color conversion layer in LCDs, addressing inefficiencies in light conversion and processability, enhancing brightness and reliability.
Patent Information
- Application Number
- JP2021020140
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-13
- Filing Date
- 2021-02-10
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2041-02-10
AI Technical Summary
Existing LCDs face challenges in achieving high color reproducibility and brightness due to limitations in light efficiency and transmission characteristics of color filters, with high power consumption and environmental issues from CCFLs, and current quantum dot compositions lack resistance to self-solvents, affecting processability and light conversion efficiency.
A self-luminous photosensitive resin composition containing quantum dots with a polyethylene glycol compound ligand, scatterers, alkali-soluble resins, photopolymerizable compounds, curing accelerators, and solvents, forming a color conversion layer that maintains film integrity and enhances light conversion efficiency and processability.
The composition achieves a uniform pattern with improved light conversion efficiency, resistance to self-solvents, and maintains quantum efficiency, resulting in better brightness and reliability of the display device.
Smart Images

Figure 0007619822000027 
Figure 0007619822000001 
Figure 0007619822000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a spontaneously luminous photosensitive resin composition, and a color conversion layer and a display device produced using the same. [Background technology]
[0002] Recently, the display industry has undergone a rapid transformation from CRT (cathode-ray tube) to flat panel displays such as PDP (plasma display panel), OLED (organic light-emitting diode), LCD (liquid-crystal display), etc. Among them, LCD is widely used as a display device in almost all industries, and its range of applications is continuously expanding.
[0003] In an LCD, the transmittance of white light generated from the backlight unit is adjusted as it passes through the liquid crystal cell, and the three primary colors that pass through the red, green, and blue color filters are mixed to produce full color.
[0004] CCFL (Cold Cathode Fluorescent Lamp) is used as the light source of the backlight unit, but in this case, power must be constantly applied to the CCFL, which causes problems with power consumption.In addition, the color reproduction rate is about 70% of that of conventional CRTs, and environmental pollution is caused by the addition of mercury.
[0005] As an alternative to resolve the above issues, currently, active research is being conducted on backlight units using LEDs (Light Emitting Diodes).When LEDs are used as backlight units, they can exceed 100% of the NTSC (National Television System Committee) color reproduction range specification, providing consumers with a more vivid picture quality.
[0006] Therefore, in order to improve the efficiency of the backlight light source, the industry is trying to improve the light efficiency by changing the materials and structures of the color filters and LCD panels, etc. However, due to the limitations of the transmission characteristics of the coloring materials, it is difficult to simultaneously satisfy color reproducibility and brightness characteristics, and a certain level cannot be exceeded.
[0007] The problem of poor color reproducibility can be resolved by increasing the light efficiency of the color filter, and therefore methods have been proposed in which the thickness of the color filter is increased or a color conversion layer (or light conversion layer) is laminated on or adjacent to it.
[0008] Figure 1 is a schematic diagram showing the role of the color conversion layer in a display device. As shown in Figure 1, the light source generated from the backlight unit can directly increase the light efficiency through the color conversion layer and the color filter.
[0009] Korean Patent No. 10-1628065 discloses an invention relating to a quantum dot complex containing an aminosiloxane-based ligand and an optical sheet containing the same. However, the current situation is that the resistance to the self-solvent cannot be ensured, and the effect of improving the light conversion efficiency and processability by ensuring the resistance to the self-solvent cannot be provided. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Republic of Korea Patent No. 10-1628065B Summary of the Invention [Problem to be solved by the invention]
[0011] The present invention has been made to solve the problems of the prior art, and aims to provide a spontaneous light-emitting photosensitive resin composition that can improve light conversion efficiency and processability to obtain a uniform pattern, and a color conversion layer and a display device manufactured using the same. [Means for solving the problem]
[0012] The present invention provides a self-luminous photosensitive resin composition comprising (A) quantum dots, (B) scatterers, (C) an alkali-soluble resin, (D) a photopolymerizable compound, (E) a curing accelerator, and (F) a solvent, characterized in that when a coating film having a thickness of 10±0.1 μm formed using the self-luminous photosensitive resin composition is precipitated in the (F) solvent at room temperature for 5 minutes, the value obtained by dividing the thickness of the coating film after precipitation by the thickness of the coating film before precipitation exceeds 0.8.
[0013] The present invention also provides a color conversion layer produced from the above-mentioned spontaneous light-emitting photosensitive resin composition.
[0014] Furthermore, the present invention provides a display device comprising the above color conversion layer. Effect of the Invention
[0015] The coating film formed using the spontaneous light-emitting photosensitive resin composition according to the present invention has excellent solvent resistance, and when the coating film is precipitated in a solvent, the value obtained by dividing the thickness of the coating film after precipitation by the thickness of the coating film before precipitation exceeds 0.8. Therefore, the color conversion layer and display device manufactured using the spontaneous light-emitting photosensitive resin composition according to the present invention have the effect of being able to obtain a uniform pattern by improving light conversion efficiency and processability.
[0016] In addition, the spontaneous light-emitting photosensitive resin composition according to the present invention contains a polyethylene glycol-based compound in the ligand layer of the quantum dot, thereby protecting the surface of the quantum dot, improving its oxidation stability, and preventing a decrease in quantum efficiency, thereby providing the effect of improving brightness and reliability. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 is a schematic diagram illustrating the role of a color conversion layer in a display device. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention relates to a spontaneous-luminous photosensitive resin composition comprising (A) quantum dots, (B) scatterers, (C) an alkali-soluble resin, (D) a photopolymerizable compound, (E) a curing accelerator, and (F) a solvent, characterized in that when a coating film having a thickness of 10±0.1 μm formed using the spontaneous-luminous photosensitive resin composition is precipitated in the (F) solvent at room temperature for 5 minutes, the thickness of the coating film after precipitation divided by the thickness of the coating film before precipitation exceeds 0.8, and to a color conversion layer and a display device manufactured using the spontaneous-luminous photosensitive resin composition.
[0019] The color conversion layer is intended to improve the light efficiency caused by the use of a color filter, and is located adjacent to the color filter (see FIG. 1) and has a fine pattern corresponding to the red (R) and green (G) patterns of the color filter. In this case, the fine pattern can be formed using a self-luminous photosensitive resin composition.
[0020] <Self-luminous photosensitive resin composition> The self-luminous photosensitive resin composition of the present invention comprises (A) quantum dots, (B) scatterers, (C) an alkali-soluble resin, (D) a photopolymerizable compound, (E) a curing accelerator, and (F) a solvent. A coating film formed using the self-luminous photosensitive resin composition of the present invention is characterized in that, when the coating film has a thickness of 10±0.1 μm and is precipitated in the (F) solvent at room temperature for 5 minutes, the coating film thickness after precipitation divided by the coating film thickness before precipitation, i.e., the film loss ratio, exceeds 0.8.
[0021] The coating film formed using the spontaneous light-emitting photosensitive resin composition according to the present invention has resistance to the original solvent (i.e., the (F) solvent) generated during the manufacturing process of the color conversion layer, and the film loss ratio exceeds 0.8, which improves the light conversion efficiency and processability of the color conversion layer and allows a uniform pattern to be obtained. If the film loss ratio is 0.8 or less, it means that the uncured part in the color conversion layer has been washed away to a certain level or more by the absorbed solvent, which may cause problems such as a decrease in the chemical and physical properties of the coating film, such as adhesion and stability.
[0022] (A) Quantum dots In the present invention, the quantum dots are capable of emitting light when stimulated by light, and are characterized by having a ligand layer containing a polyethylene glycol compound on the surface.
[0023] As an example, the polyethylene glycol-based compound may include a compound represented by the following chemical formula 1. By including a specific compound in the ligand layer, the surface of the quantum dots is protected, the oxidation stability is improved, and a decrease in quantum efficiency is prevented, thereby improving brightness and reliability.
[0024] [ka]
[0025] (In the above Chemical Formula 1, R' is represented by the following chemical formula 1-1: R" is a hydrogen atom or a mercapto group. TIFF0007619822000002.tif13141
[0026] , carboxy group TIFF0007619822000003.tif18141
[0027] , dithioacetate group TIFF0007619822000004.tif18141
[0028] , phosphate group TIFF0007619822000005.tif25141
[0029] , an amine group (-NH2), a linear alkyl group having 1 to 20 carbon atoms, or a branched alkyl group having 3 to 20 carbon atoms; k is an integer from 1 to 100,
[0030] [ka]
[0031] In the above Chemical Formula 1-1, R 1 is a direct linking group or an alkylene group having 1 to 10 carbon atoms, R 2 is represented by the following chemical formula 1-2,
[0032] [ka]
[0033] In the above Chemical Formula 1-2, A is an oxygen atom or a sulfur atom, R 3 is a direct linking group or an alkylene group having 1 to 10 carbon atoms, B is a mercapto group TIFF0007619822000008.tif17140
[0034] , carboxy group TIFF0007619822000009.tif19141
[0035] , dithioacetate group TIFF0007619822000010.tif19141
[0036] , phosphate group TIFF0007619822000011.tif25141
[0037] or an amine group (-NH2), l is an integer from 0 to 1; m is an integer from 0 to 10. The quantum dots can be used without any limitation as long as they have a ligand layer containing a polyethylene glycol-based compound on the surface thereof. For example, one or more types selected from II-VI group semiconductor compounds, III-V group semiconductor compounds, IV-VI group semiconductor compounds, and Group IV elements, or compounds containing these, can be used.
[0038] Specific examples of the compound represented by Chemical Formula 1 include, but are not limited to, 2-(2-methoxyethoxy)acetic acid (WAKO), 2-[2-(2-methoxyethoxy)ethoxy]acetic acid (WAKO), {2-[2-(carboxymethoxy)ethoxy]ethoxy}acetic acid (WAKO), 2-[2-(benzyloxy)ethoxy]acetic acid, (2-(carboxymethoxy)ethoxy)acetic acid (WAKO), (2-butoxyethoxy)acetic acid (WAKO), and carboxy-EG6-undecanethiol.
[0039] In addition, the quantum dots may have a homogeneous single structure, a double structure such as a core-shell structure, a gradient structure, or a mixture of these structures. For example, in the core-shell double structure, the materials constituting the core and the shell may be made of the above-mentioned semiconductor compounds different from each other.
[0040] The core can comprise one or more selected from the group consisting of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb, and the shell can comprise one or more selected from the group consisting of ZnSe, ZnS, and ZnTe.
[0041] Just as a colored photosensitive resin composition used in the manufacture of a typical color filter contains red, green, and blue colorants to achieve a desired hue, the quantum dots of the present invention can also be classified into red quantum dots, green quantum dots, and blue quantum dots, and the quantum dots of the present invention may be one or more types selected from the above-mentioned red, green, and blue quantum dots.
[0042] The total content of the quantum dots is not particularly limited in the present invention, but is preferably 1 to 60% by weight, and more preferably 2 to 50% by weight, based on 100% by weight of the total solid content of the light-converting resin composition. When the quantum dots are contained within the above range, there are advantages in that the light-emitting efficiency is excellent and the reliability of the coating layer is excellent. When the quantum dots are contained below the above range, the light conversion efficiency of green light and red light is insufficient, and when the quantum dots are contained above the above range, the emission of blue light is relatively reduced, resulting in a problem of poor color reproducibility, so it is preferable to satisfy the above range.
[0043] (B) Scatterer In the present invention, the scatterer is used to improve the luminous efficiency. The light emitted from the light source is incident on the color filter at a critical angle, and at this time, the incident light and the self-emitted light emitted by the quantum dots themselves come into contact with the scatterer, and the luminous intensity is increased due to the increase in the light path, resulting in an improvement in the luminous efficiency.
[0044] The scatterers can be metal oxide particles having an average particle size of 30 to 500 nm. When the average particle size of the scatterers is within the above range, a fine pattern can be formed with excellent properties, sufficient scattering effect of incident light can be expected, and the problem of sinking in the composition does not occur, so that a self-luminous layer surface of uniform quality can be obtained, which is preferable.
[0045] As an embodiment, the scatterer may be one or more selected from the group consisting of Al2O3, SiO2, ZnO, ZrO2, BaTiO3, TiO2, Ta2O5, Ti3O5, ITO, IZO, ATO, ZnO-Al, Nb2O3, SnO, MgO, and combinations thereof. If necessary, a material that has been surface-treated with a compound having an unsaturated bond, such as acrylate, may also be used.
[0046] The scattering particles are contained in an amount of 0.5 to 20% by weight, preferably 1 to 15% by weight, based on the total weight of the solid content in the composition. When the scattering particles are contained within the above range, the effect of increasing the luminous intensity can be maximized, which is preferable, when the scattering particles are contained below the above range, it is somewhat difficult to secure the desired luminous intensity, and when the scattering particles are contained above the above range, the transmittance of blue irradiation light is reduced, which may cause problems in luminous efficiency.
[0047] (C) Alkali-soluble resin In the present invention, the alkali-soluble resin has reactivity due to the action of light or heat and alkali-solubility, and acts as a dispersion medium for the coloring material.
[0048] The alkali-soluble resin comprises a reactive alkali-soluble resin (C1) which is reactive to a curing accelerator (E) and UV irradiation described below; and a non-reactive alkali-soluble resin (C2) which is non-reactive to a curing accelerator (E) and UV irradiation described below, and the mixing weight ratio of the reactive alkali-soluble resin (C1) to the non-reactive alkali-soluble resin (C2) is 7:3 to 3:7.
[0049] This ensures resistance to the solvent generated during the manufacturing process of the color conversion layer, and improves light conversion efficiency and processability to obtain a uniform pattern. In the present invention, "resistance to the solvent" refers to resistance to the solvent (F) contained in the self-luminous photosensitive resin composition according to the present invention, and is understood to mean the chemical stability of the light conversion layer exposed to the solvent. Specifically, when a composition is applied to form a secondary light conversion layer after the primary light conversion layer process, the composition comes into contact with the top of the primary light conversion layer and is then removed by a post-process. At this time, if the degree of crosslinking or uniformity of the primary light conversion layer decreases, the solvent in the composition is absorbed, the uniformity of the coating film decreases, and chemical and physical modifications occur. Therefore, by adjusting the ratio of the reactive alkali-soluble resin and the non-reactive alkali-soluble resin, the degree of crosslinking of the coating film can be increased to prevent the phenomenon of the solvent penetrating.
[0050] The (C1) reactive alkali-soluble resin contains a (C1-1) compound and a (C1-2) compound, and may be a copolymer obtained by polymerization of the (C1-1) compound and the (C1-2) compound, or may be a copolymer obtained by further polymerizing the following (C1-3) compound.
[0051] The (C1-1) compound contained in the (C1) reactive alkali-soluble resin is a compound having an unsaturated bond and a carboxylic acid group in one molecule, and is not limited as long as it is a carboxylic acid compound having a polymerizable unsaturated double bond, and each can be used alone or in combination of two or more. Specific examples include monocarboxylic acids such as acrylic acid, methacrylic acid, and crotonic acid; dicarboxylic acids such as fumaric acid, mesaconic acid, and itaconic acid; and anhydrides of the dicarboxylic acids; mono(meth)acrylates of polymers having a carboxyl group and a hydroxyl group at both ends, such as ω-carboxypolycaprolactone mono(meth)acrylate. Acrylic acid and methacrylic acid in the compounds are preferred because they have excellent copolymerization reactivity and solubility in a developer.
[0052] The (C1-2) compound contained in the (C1) reactive alkali-soluble resin is a compound having an unsaturated bond polymerizable with (C1-1), and any compound having a polymerizable unsaturated double bond can be used without limitation. Specific examples include unsubstituted or substituted alkyl ester compounds of unsaturated carboxylic acids such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, and aminoethyl (meth)acrylate; and alicyclic substituents such as cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, methylcyclohexyl (meth)acrylate, cycloheptyl (meth)acrylate, cyclooctyl (meth)acrylate, pentyl (meth)acrylate, cyclopentenyl (meth)acrylate, cyclohexenyl (meth)acrylate, cycloheptenyl (meth)acrylate, cyclooctenyl (meth)acrylate, pentadienyl (meth)acrylate, isobornyl (meth)acrylate, pinanyl (meth)acrylate, adamantyl (meth)acrylate, norbornyl (meth)acrylate, and pinenyl (meth)acrylate. unsaturated carboxylic acid ester compounds containing 3-((meth)acryloyloxymethyl)oxetane, 3-((meth)acryloyloxymethyl)-3-ethyloxetane, 3-((meth)acryloyloxymethyl)-2-methyloxetane, 3-((meth)acryloyloxymethyl)-2-trifluoromethyloxetane and other heat-curable substituent-containing unsaturated carboxylic acid ester compounds; monosaturated carboxylic acid ester compounds of glycols such as oligoethylene glycol monoalkyl (meth)acrylate; unsaturated carboxylic acid ester compounds containing aromatic ring-containing substituents such as benzyl (meth)acrylate and phenoxy (meth)acrylate; aromatic vinyl compounds such as styrene, α-methylstyrene, and vinyl toluene; vinyl carboxylate esters such as vinyl acetate and vinyl propionate; and vinyl cyanide compounds such as (meth)acrylonitrile and α-chloroacrylonitrile. Among these, aromatic vinyl compounds are preferred for improving sensitivity and reducing outgassing. These can be used alone or in combination of two or more.
[0053] The (C1-3) compound contained in the (C1) reactive alkali-soluble resin is a compound having an unsaturated bond and an epoxy group in one molecule, and the unsaturated bond can be provided by a (meth)acrylic group. Specific examples include glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and methylglycidyl (meth)acrylate. Of these, glycidyl (meth)acrylate is preferably used. These can be used alone or in combination of two or more.
[0054] The (C2) non-reactive alkali-soluble resin used in the present invention includes a (C2-1) compound and a (C2-2) compound, and can be prepared in the same manner as the (C1) reactive alkali-soluble resin. However, since the (C2) non-reactive alkali-soluble resin must be polymerized without an unsaturated double bond in the molecular chain that can be photopolymerized by UV irradiation and a curing accelerator, the process of copolymerizing the (C1-3) compound contained in the (C1) reactive alkali-soluble resin is omitted, and the (C2-1) compound and the (C2-2) compound are copolymerized. The method is the same as the general synthesis example of the (C1) reactive alkali-soluble resin, and the (C2-1) compound and the (C2-2) compound can be the substances exemplified as the (C1-1) compound and the (C1-2) compound, respectively.
[0055] The alkali-soluble resin is contained in an amount of 5 to 85% by weight, preferably 20 to 85% by weight, and more preferably 40 to 75% by weight, based on the total weight of the solid content in the composition. When the content of the alkali-soluble resin is within the above range, it is possible to ensure resistance to the self-solvent generated in the manufacturing process of the color conversion layer, and it is possible to obtain a uniform pattern by improving the light conversion efficiency and processability, which is preferable.
[0056] (D) Photopolymerizable compound In the present invention, the photopolymerizable compound is a compound that can be polymerized by the action of a curing accelerator described below, and examples of the photopolymerizable compound include monofunctional monomers, bifunctional monomers, and other polyfunctional monomers.
[0057] Specific examples of the monofunctional monomer include nonylphenylcarbitol acrylate, 2-hydroxy-3-phenoxypropyl acrylate, 2-ethylhexylcarbitol acrylate, 2-hydroxyethyl acrylate, and N-vinylpyrrolidone.
[0058] Specific examples of bifunctional monomers include 1,6-hexanediol di(meth)acrylate, ethylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, bis(acryloyloxyethyl)ether of bisphenol A, and 3-methylpentanediol di(meth)acrylate.
[0059] Specific examples of other polyfunctional monomers include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, etc. Among these, bifunctional or higher polyfunctional monomers are preferably used.
[0060] The photopolymerizable compound is contained in an amount of 10 to 90% by weight, preferably 20 to 90% by weight, and more preferably 30 to 80% by weight, based on the total weight of the solid content in the composition. When the content of the photopolymerizable compound is within the above range, the strength and smoothness of the pixel portion tend to be improved, which is preferable.
[0061] (E) Curing accelerator The light-converting resin composition according to the present invention may contain a curing accelerator.
[0062] The curing accelerator is preferably, for example, one or more compounds selected from the group consisting of carboxylic acid compounds, organic sulfur compounds having a thiol group, and acid generators, but is not limited thereto.
[0063] The carboxylic acid compound is preferably an aromatic heteroacetic acid, and specific examples thereof include phenylthioacetic acid, methylphenylthioacetic acid, ethylphenylthioacetic acid, methylethylphenylthioacetic acid, dimethylphenylthioacetic acid, methoxyphenylthioacetic acid, dimethoxyphenylthioacetic acid, chlorophenylthioacetic acid, dichlorophenylthioacetic acid, N-phenylglycine, phenoxyacetic acid, naphthylthioacetic acid, N-naphthylglycine, naphthoxyacetic acid, and 1,2,4-benzenetricarboxylic acid anhydride, but are not limited thereto.
[0064] Specific examples of the organic sulfur compound having a thiol group include, but are not limited to, 2-mercaptobenzothiazole, 1,4-bis(3-mercaptobutyryloxy)butane, 1,3,5-tris(3-mercaptobutyloxyethyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), pentaerythritol tetrakis(3-mercaptopropionate), dipentaerythritol hexakis(3-mercaptopropionate), and tetraethylene glycol bis(3-mercaptopropionate).
[0065] Specific examples of the acid generator include onium salts such as 4-hydroxyphenyl dimethyl sulfonium p-toluenesulfonate, 4-hydroxyphenyl dimethyl sulfonium hexafluoroantimonate, 4-acetoxyphenyl dimethyl sulfonium p-toluenesulfonate, 4-acetoxyphenyl methyl benzyl sulfonium hexafluoroantimonate, triphenyl sulfonium p-toluenesulfonate, triphenyl sulfonium hexafluoroantimonate, diphenyl iodonium p-toluenesulfonate, and diphenyl iodonium hexafluoroantimonate; nitrobenzyl tosylates; and benzoin tosylates.
[0066] Commercially available products of the hardening accelerator include, but are not limited to, RIKACID HH (manufactured by New Japan Chemical Co., Ltd.), trade name (ADEKA HARDNER EH-700) (manufactured by Adeka Kogyo Co., Ltd.), trade name (MH-700) (manufactured by New Japan Chemical Co., Ltd.), and the like.
[0067] The curing accelerator is contained in an amount of 0.1 to 40% by weight, preferably 1 to 30% by weight, based on the total weight of the solid content in the composition. When the content of the curing accelerator is within the above range, the photoconversion resin composition containing the curing accelerator is highly sensitive and the curing time of the coating film is shortened, which has the advantage of improving productivity and realizing high reliability, and the strength of the coating film formed using the curing accelerator and the surface smoothness of the coating film are improved. On the other hand, when the content of the curing accelerator is less than the above range, the decrease in the curing degree cannot be overcome, and wrinkles may occur during the subsequent process, and when the content exceeds the above range, there is a problem that the light-emitting properties of the photoconversion resin composition are decreased and the brightness is insufficient.
[0068] (F) Solvent In the present invention, the solvent may be any organic solvent commonly used in the art, without any particular limitation. Examples of the solvent include ethers, acetates, aromatic hydrocarbons, ketones, alcohols, and esters, and one or more of these may be selected for use, but are not limited thereto.
[0069] From the viewpoint of coatability and drying property, it is preferable to use an organic solvent having a boiling point of 100° C. to 200° C. in the solvent, more preferably, alkylene glycol alkyl ether acetates, ketones, esters such as ethyl 3-ethoxypropionate and methyl 3-methoxypropionate can be used, and even more preferably, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, cyclohexanone, ethyl 3-ethoxypropionate, methyl 3-methoxypropionate, etc. These solvents can be used alone or in combination of two or more kinds.
[0070] The solvent is included in an amount sufficient to make the total weight of the composition 100% by weight. Specifically, in the present invention, the term "balance" refers to an amount sufficient to make the total weight of the composition, including the essential components of the present invention and other additional components, 100% by weight, and the meaning of the "balance" does not limit the composition of the present invention to the absence of additional components.
[0071] In one embodiment, the content of the solvent is 60 to 90% by weight, preferably 70 to 85% by weight, based on the total weight of the composition. When the content of the solvent is within the above range, the coating property tends to be good when the composition is coated with a coating device such as a roll coater, a spin coater, a slit and spin coater, a slit coater (sometimes called a die coater), or an inkjet, which is preferable.
[0072] <Color conversion layer> The present invention also provides a color conversion layer produced from the spontaneous light emitting photosensitive resin composition.
[0073] When the color conversion layer of the present invention is applied to a display device, it can achieve better light efficiency since it emits light by the light source of the display device, and since it emits light having a hue, it has better color reproducibility, and since light is emitted in all directions by photoluminescence, it can also improve the viewing angle.
[0074] More specifically, in a conventional display device including a color conversion layer, white light is transmitted through the color conversion layer to realize color, but during this process, a portion of the light is absorbed by the color conversion layer, which can reduce light efficiency. However, in the case of a display device including a color conversion layer made of the self-luminous photosensitive resin composition of the present invention, the color conversion layer emits light by itself due to the light from a light source, so that a better light efficiency can be realized.
[0075] The color conversion layer includes a substrate and a pattern layer formed on the substrate. The substrate may be the substrate of the color conversion layer itself, or may be a portion of a display device where the color conversion layer is located, and is not particularly limited. The substrate may be made of glass, silicon (Si), silicon oxide (SiO x ), or a polymer substrate, and the polymer substrate may be polyethersulfone (PES) or polycarbonate (PC), etc.
[0076] The pattern layer is a layer containing the spontaneous light-emitting photosensitive resin composition of the present invention, and may be a layer formed by applying the spontaneous light-emitting photosensitive resin composition, exposing it to a predetermined pattern, developing it, and thermally curing it.
[0077] The pattern layer formed of the self-luminous photosensitive resin composition may include a red pattern layer containing red quantum dot particles, a green pattern layer containing green quantum dot particles, and a blue pattern layer containing blue quantum dot particles. When irradiated with light, the red pattern layer emits red light, the green pattern layer emits green light, and the blue pattern layer emits blue light. In this case, when applied to a display device, the emitted light of the light source is not particularly limited, but a light source that emits blue light can be used in terms of better color reproducibility.
[0078] According to another embodiment of the present invention, the pattern layer may include only two color pattern layers among a red pattern layer, a green pattern layer, and a blue pattern layer, in which case the pattern layer further includes a transparent pattern layer that does not contain quantum dot particles.
[0079] When only two pattern layers of different hues are provided, a light source that emits light of a wavelength that represents the remaining hue that is not included can be used. For example, when a red pattern layer and a green pattern layer are provided, a light source that emits blue light can be used. In this case, the red quantum dot particles emit red light, the green quantum dot particles emit green light, and the transparent pattern layer transmits the blue light as it is, thereby showing blue color.
[0080] The color conversion layer including the substrate and the pattern layer may further include a partition formed between each pattern, may further include a black matrix, and may further include a protective film formed on the pattern layer of the color conversion layer.
[0081] <Display device> The present invention also provides a display device including the color conversion layer.
[0082] The color conversion layer of the present invention is applicable not only to ordinary liquid crystal displays but also to various image displays such as electroluminescent displays, plasma displays, and field emission displays.
[0083] The display device of the present invention may include a color conversion layer including a red pattern layer containing red quantum dot particles, a green pattern layer containing green quantum dot particles, and a blue pattern layer containing blue quantum dot particles. In this case, when applied to the display device, the light emitted from the light source is not particularly limited, but from the viewpoint of better color reproducibility, a light source that emits blue light can be preferably used.
[0084] According to another embodiment of the present invention, the display device of the present invention may include a color conversion layer including only two hue pattern layers among a red pattern layer, a green pattern layer, and a blue pattern layer, in which case the color conversion layer further includes a transparent pattern layer that does not contain quantum dot particles.
[0085] When only two pattern layers of different hues are provided, a light source that emits light of a wavelength that represents the remaining hue that is not included can be used. For example, when a red pattern layer and a green pattern layer are provided, a light source that emits blue light can be used. In this case, the red quantum dot particles emit red light, the green quantum dot particles emit green light, and the transparent pattern layer transmits the blue light as it is, thereby showing blue color.
[0086] The display device of the present invention has excellent light efficiency, exhibits high luminance, has excellent color reproducibility, and can have a wide viewing angle. EXAMPLES
[0087] The present invention will be described in more detail below using examples and comparative examples. However, the following examples are for illustrating the present invention, and the present invention is not limited to the following examples, and various modifications and changes can be made. The scope of the present invention is defined by the technical ideas of the claims described below. In addition, "%" and "parts" indicating the contents below are based on weight unless otherwise specified.
[0088] Preparation of scattering particle dispersion Production Example 1: Production of scattering particle dispersion S-1 70.0 parts by weight of TiO2 (Huntsman's TTO-55(C)) with a particle size of 30 nm as scattering particles, 4.0 parts by weight of DISPERBYK-2001 (manufactured by BYK) as a dispersant, and 26 parts by weight of propylene glycol methyl ether acetate as a solvent were mixed / dispersed for 12 hours using a bead mill to produce scattering particle dispersion S-1.
[0089] Synthesis Example 1: Synthesis of quantum dots (Q-1) 0.4 mmol (0.058 g) of indium acetate, 0.6 mmol (0.15 g) of palmitic acid, and 20 mL of 1-octadecene were placed in a reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was switched to nitrogen. After heating to 280°C, a mixed solution of 0.2 mmol (58 μl) of tris(trimethylsilyl)phosphine (TMS3P) and 1.0 mL of trioctylphosphine was quickly injected and reacted for 1 minute.
[0090] Next, 2.4 mmol (0.448 g) of zinc acetate, 4.8 mmol of oleic acid, and 20 mL of trioctylamine were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was switched to nitrogen, and the reactor was heated to 280°C. 2 mL of the previously synthesized InP core solution was added, followed by 4.8 mmol of selenium in trioctylphosphine (Se / TOP), and the final mixture was reacted for 2 hours. Ethanol was added to the reaction solution, which was quickly cooled to room temperature, and the precipitate obtained by centrifugation was filtered under reduced pressure and dried under reduced pressure to form an InP / ZnSe core-shell.
[0091] Next, 2.4 mmol (0.448 g) of zinc acetate, 4.8 mmol of oleic acid, and 20 mL of trioctylamine were added to the reactor and heated to 120°C under vacuum. After 1 hour, the atmosphere in the reactor was switched to nitrogen, and the reactor was heated to 280°C. 2 mL of the previously synthesized InP core solution was added, followed by 4.8 mmol of sulfur in trioctylphosphine (S / TOP), and the final mixture was reacted for 2 hours. The reaction solution was quickly cooled to room temperature, and ethanol was added, followed by centrifugation to obtain a precipitate, which was then filtered under reduced pressure and dried under reduced pressure to obtain InP / ZnSe / ZnS core-shell structured quantum dots, which were then dispersed in chloroform.
[0092] The maximum emission peak of the optical emission spectrum of the obtained nano quantum dots was 525 nm. 5 mL of the quantum dot solution was placed in a centrifuge tube and precipitated by adding 20 mL of ethanol. The supernatant was discarded by centrifugation, and 2 mL of chloroform was added to the precipitate to disperse the quantum dots. Then, 0.50 g of (2-butoxy-ethoxy)-acetic acid was added and reacted for 1 hour while heating to 60 ° C under a nitrogen atmosphere.
[0093] Next, 25 mL of n-hexane was added to the reaction mixture to precipitate the quantum dots, and the precipitate was separated by centrifugation. 4 mL of propylene glycol monomethyl ether acetate was then added and dispersed by heating to 80°C. The solid content was adjusted to 25% by weight with PGMEA. The maximum emission wavelength was 524 nm.
[0094] Synthesis Example 2: Synthesis of quantum dots (Q-2) 5 mL of the quantum dot solution dispersed in chloroform synthesized in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to cause precipitation. The supernatant was discarded after centrifugation, and 2 mL of chloroform was added to the precipitate to disperse the quantum dots, after which 0.5 g of O-(Succinyl)-O'-methylpolyethylene glycol 2'000 (Aldrich) was added and reacted for 1 hour while heating to 60°C under a nitrogen atmosphere.
[0095] Next, 25 mL of n-hexane was added to the reaction mixture to precipitate the quantum dots, and the precipitate was separated by centrifugation. 4 mL of propylene glycol monomethyl ether acetate was then added and dispersed by heating to 80°C. The solid content was adjusted to 25 wt% with PGMEA. The maximum emission wavelength was 525 nm.
[0096] Synthesis Example 3: Synthesis of quantum dots (Q-3) 5 mL of the quantum dot solution dispersed in chloroform synthesized in Synthesis Example 1 was placed in a centrifuge tube, and 20 mL of ethanol was added to cause precipitation. The supernatant was discarded by centrifugation, and 2 mL of chloroform was added to the precipitate to disperse the quantum dots, after which 0.65 g of Carboxy-EG6-undecanethiol (Aldrich) was added and reacted for 1 hour while heating to 60°C under a nitrogen atmosphere.
[0097] Next, 25 mL of n-hexane was added to the reaction mixture to precipitate the quantum dots, and the precipitate was separated by centrifugation. 4 mL of propylene glycol monomethyl ether acetate was then added and dispersed while heating to 80°C. The solid content was adjusted to 25 wt% with PGMEA. The maximum emission wavelength was 534 nm.
[0098] Synthesis Example 4: Synthesis of reactive alkali-soluble resin C-1-1 A flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube was prepared. On the other hand, 45 parts by weight of N-benzylmaleimide, 45 parts by weight of methacrylic acid, 10 parts by weight of tricyclodecyl methacrylate, 4 parts by weight of t-butylperoxy-2-ethylhexanoate, and 40 parts by weight of propylene glycol monomethyl ether acetate (hereinafter referred to as "PGMEA") were added, and then stirred and mixed to prepare a monomer dropping funnel. 6 parts by weight of n-dodecanethiol and 24 parts by weight of PGMEA were added, and then stirred and mixed to prepare a chain transfer agent dropping funnel. After that, 395 parts by weight of PGMEA were introduced into the flask, and the atmosphere in the flask was changed from air to nitrogen, and the temperature of the flask was raised to 90°C while stirring. Next, the monomer and the chain transfer agent were started to be dropped from the dropping funnel. The dropping was continued for 2 hours while maintaining the temperature at 90°C, and after 1 hour, the temperature was raised to 110°C and maintained for 3 hours, after which a gas inlet tube was introduced to start bubbling a mixed gas of oxygen / nitrogen = 5 / 95 (v / v). Next, 10 parts by weight of glycidyl methacrylate, 0.4 parts by weight of 2,2'-methylenebis(4-methyl-6-t-butylphenol), and 0.8 parts by weight of triethylamine were added to the flask, and the reaction was continued at 110°C for 8 hours, and then the mixture was cooled to room temperature to obtain resin C-1-1 having a solid content of 29.1% by weight, a weight average molecular weight of 32,000, and an acid value of 114 mgKOH / g.
[0099] Synthesis Example 5: Synthesis of non-reactive alkali-soluble resin C-2-1 A flask equipped with a stirrer, thermometer, reflux condenser, dropping funnel, and nitrogen inlet tube was prepared, and 300 parts by weight of propylene glycol monomethyl ether acetate (PGMEA) was added, followed by heating to 75°C while stirring. A solution of 62.5 parts by weight of 3,4-epoxy-8-(acryloyloxy)tricyclo[5.2.1.02,6]decane (EDCPA), 15.1 parts by weight of acrylic acid (AA), and 22.4 parts by weight of vinyltoluene dissolved in 170 parts by weight of PGMEA was added dropwise to the flask using a dropping funnel for 5 hours. Meanwhile, a solution of 30 parts by weight of the polymerization initiator azobisisobutyronitrile dissolved in 200 parts by weight of PGMEA was added dropwise using another dropping funnel for 5 hours. After the dropwise addition of the polymerization initiator was completed, the temperature was maintained for about 4 hours, and then the mixture was cooled to room temperature to obtain Resin C-2-1 having a solid content of 37.6% by weight, a weight average molecular weight of 10,740, and an acid value of 111 mgKOH / g.
[0100] Synthesis Example 6: Synthesis of reactive alkali-soluble resin C-1-2 Into a flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube, 120 g of propylene glycol monomethyl ether acetate, 80 g of propylene glycol monomethyl ether, 2 g of 2,2'-azobisisobutyronitrile, 20 g of acrylic acid, 30.0 g of benzyl acrylate, 50 g of methyl methacrylate, and 3 g of n-dodecyl mercaptan were placed, and the inside of the flask was replaced with nitrogen.
[0101] The temperature of the reaction solution was then raised to 80° C. with stirring, and the reaction was carried out for 8 hours. The acid value of the solid content of the alkali-soluble resin C-1-2 thus synthesized was 158 mg KOH / g, and the weight average molecular weight Mw measured by GPC was about 12,874, and the polydispersity (Mw / Mn) was 2.81.
[0102] Synthesis Example 7: Synthesis of non-reactive alkali-soluble resin C-2-2 79 g of methoxybutyl acetate was added to a 0.5 L separatory flask equipped with a stirrer, a thermometer, a reflux condenser, a dropping funnel, and a nitrogen inlet tube, and the temperature was raised to 80°C. Then, 60 g of a mixture of 3,4-epoxytricyclo[5.2.1.02,6]decan-9-yl acrylate and 3,4-epoxytricyclo[5.2.1.02,6]decan-8-yl acrylate [50:50 (molar ratio)] (E-DCPA), 20 g of methacrylic acid, 20 g of hydroxyethyl methacrylate, and 6.5 g of azobisdimethylvaleronitrile were dissolved in 100 g of methoxybutyl acetate. The mixture was then dropped over 5 hours, and the mixture was aged for another 3 hours to obtain a copolymer solution [solid content (NV) 35.0 wt%]. The resulting resin C-2-2 had an acid value (dry) of 135.8 mgKOH / g, a weight average molecular weight (Mw) of 13,500, and a polydispersity (Mw / Mn) of 2.11.
[0103] Examples 1 to 12 and Comparative Examples 1 to 6: Production of photoconversion resin compositions Photoconverting resin compositions according to examples and comparative examples were prepared using the components and contents (wt %) in Tables 1 and 2 below.
[0104] [Table 1]
[0105] [Table 2]
[0106] Experimental Example A light-conversion coating layer was prepared as described below using the light-conversion resin compositions prepared in the above examples and comparative examples, and the brightness, light retention rate, heat resistance and coating hardness were measured by the following methods. The evaluation results are shown in Table 3 below.
[0107] (1) Manufacturing of light conversion coating layer A coating film was prepared using the light-converting resin compositions prepared in the examples and comparative examples. That is, each light-converting resin composition was applied onto a 5 cm x 5 cm glass substrate by spin coating, and then placed on a heating plate and maintained at 100°C for 10 minutes to form a thin film, and then heated in a heating oven at 180°C for 30 minutes to prepare a light-converting coating layer. The thickness of the light-converting resin film prepared above was adjusted to 10 μm depending on the content of quantum dots.
[0108] (2) Luminance evaluation The coating film prepared in (1) was placed on top of a blue light source (XLamp XR-E LED, Royal blue 450, Cree), and the brightness was measured using a brightness meter (CAS140CT Spectrometer, Instrument Systems), and the evaluation results are shown in Table 3 below.
[0109] (3) Light maintenance rate The coated substrate prepared by the method for manufacturing the light conversion coating layer was hard baked at 230°C for 60 minutes, and the luminous efficiency before and after the hard bake was measured to confirm the level at which the luminous efficiency was maintained. The evaluation results are shown in Table 3 below.
[0110] (4) Sedimentation shrinkage rate (film loss rate) After forming the coating film in (1) above, the change in thickness after autogenous precipitation was confirmed using the following formula 1. Specifically, the final coating film was precipitated in (F) solvent (propylene glycol monomethyl ether acetate) at room temperature for 5 minutes, and the thicknesses before and after precipitation were measured, and the rate of change (shrinkage rate) was calculated using the following formula 1, and the results are shown in Table 3 below.
[0111]
number
[0112] (5) Paint film hardness The degree of hardness of the coating film prepared in (1) above was measured at a high temperature of 150°C using a hardness tester (HM500; product of Fischer), and the surface hardness (coating film hardness) was evaluated according to the following criteria. The results are shown in Table 3 below.
[0113] <Evaluation criteria> ○: Surface hardness 20 or more △: Surface hardness 10 or more and less than 20 ×: Surface hardness less than 10
[0114] [Table 3]
[0115] As shown in Table 3, the light-conversion sheets having a thickness of 10±0.1 μm formed from the light-conversion resin compositions of Examples 1 to 12 containing quantum dots having a ligand of Chemical Formula 1 according to the present invention and a certain proportion of reactive and non-reactive binders were confirmed to have a coating film precipitation shrinkage rate (film loss rate) of more than 0.8, and therefore had excellent brightness, optical properties, and coating hardness, which were even more excellent in brightness, optical properties, and coating hardness than Comparative Examples 1 to 6, which had film loss rates of 0.8 or less.
[0116] Although specific parts of the present invention have been described in detail above, it is clear to those skilled in the art that such specific descriptions are merely preferred embodiments and do not limit the scope of the present invention. Those skilled in the art will be able to make various applications and modifications within the scope of the present invention based on the above content.
[0117] Therefore, the true scope of the invention is to be defined by the appended claims and their equivalents.
Claims
1. A spontaneous light-emitting photosensitive resin composition comprising: (A) quantum dots; (B) a scatterer; (C) an alkali-soluble resin; (D) a photopolymerizable compound; (E) a curing accelerator; and (F) a solvent, When a coating film having a thickness of 10±0.1 μm formed using the spontaneous light-emitting photosensitive resin composition is precipitated in the (F) solvent at room temperature for 5 minutes, the value obtained by dividing the thickness of the coating film after precipitation by the thickness of the coating film before precipitation exceeds 0.8, The (A) quantum dot is InP / ZnSe / ZnS and has a ligand layer containing a polyethylene glycol compound on the surface; The (C) alkali-soluble resin includes a (C1) reactive alkali-soluble resin that is reactive to the (E) curing accelerator and UV irradiation, and a (C2) non-reactive alkali-soluble resin that is non-reactive to the (E) curing accelerator and UV irradiation, A spontaneous light-emitting photosensitive resin composition, characterized in that the mixing weight ratio of the reactive alkali-soluble resin (C1) to the non-reactive alkali-soluble resin (C2) is 7:3 to 3:
7.
2. The self-luminous photosensitive resin composition according to claim 1 , wherein the polyethylene glycol-based compound includes a compound represented by the following Chemical Formula 1: 【Chemistry 1】 (In the above Chemical Formula 1, R' is represented by the following chemical formula 1-1: R" is a hydrogen atom or a mercapto group. 【change】 , carboxy group 【change】 , dithioacetate group 【change】 , phosphate group 【change】 , amine group (-NH 2 ), a linear alkyl group having 1 to 20 carbon atoms, or a branched alkyl group having 3 to 20 carbon atoms; k is an integer from 1 to 100; 【Chemistry 1-1】 In the above Chemical Formula 1-1, R 1 is a direct linking group or an alkylene group having 1 to 10 carbon atoms, R 2 is represented by the following chemical formula 1-2, 【Chemistry 1-2】 In the above Chemical Formula 1-2, A is an oxygen atom or a sulfur atom, R 3 is a direct linking group or an alkylene group having 1 to 10 carbon atoms, B is a mercapto group 【change】 , carboxy group 【change】 , dithioacetate group 【change】 , phosphate group 【change】 , or an amine group (-NH 2 ) and l is an integer from 0 to 1; m is an integer from 0 to 10.
3. the (C1) reactive alkali-soluble resin contains a (C1-1) compound and a (C1-2) compound, and the (C2) non-reactive alkali-soluble resin contains a (C2-1) compound and a (C2-2) compound, the (C1-1) and (C2-1) each independently comprise at least one selected from the group consisting of monocarboxylic acids, dicarboxylic acids, anhydrides of the dicarboxylic acids, and mono(meth)acrylates of polymers having a carboxyl group and a hydroxyl group at both ends; The self-luminous photosensitive resin composition according to claim 1, wherein (C1-2) and (C2-2) each independently comprise one or more selected from the group consisting of unsubstituted or substituted alkyl ester compounds of unsaturated carboxylic acids, unsaturated carboxylic acid ester compounds containing an alicyclic substituent, unsaturated carboxylic acid ester compounds containing a thermosetting substituent, monosaturated carboxylic acid ester compounds of glycols, unsaturated carboxylic acid ester compounds containing a substituent having an aromatic ring, aromatic vinyl compounds, vinyl carboxylate esters, and vinyl cyanide compounds.
4. The self-luminous photosensitive resin composition according to claim 3, wherein the reactive alkali-soluble resin (C1) further comprises one or more compounds (C1-3) selected from the group consisting of glycidyl (meth)acrylate, 3,4-epoxycyclohexyl (meth)acrylate, 3,4-epoxycyclohexylmethyl (meth)acrylate, and methylglycidyl (meth)acrylate.
5. 2. The spontaneously luminous photosensitive resin composition according to claim 1, wherein the (F) solvent is at least one selected from the group consisting of ethers, acetates, aromatic hydrocarbons, ketones, and esters.
6. Based on the total weight of solids in the composition, (A) 1-60% by weight of quantum dots; (B) 0.5 to 20% by weight of scatterer; (C) 20 to 85% by weight of an alkali-soluble resin; (D) 20 to 90% by weight of photopolymerizable compound; (E) 0.1 to 40% by weight of a curing accelerator; and 2. The spontaneously luminous photosensitive resin composition according to claim 1, further comprising a balance of (F) a solvent so that the total weight of the composition is 100% by weight.
7. A color conversion layer produced from the spontaneous light emitting photosensitive resin composition according to any one of claims 1 to 6.
8. A display device comprising the color conversion layer according to claim 7.
Citation Information
Patent Citations
Light-converting resin composition, light-converting laminated substrate, and image display device using the same
JP2019174804A
Self-luminous photosensitive resin composition, color filter and image display device manufactured using the same
JP2020500238A
Luminescence complex, composition including the complex, hardened member of the composition, optical sheet, backlight unit, and display device
KR101628065B1
Composition containing fluorescent particles, wavelength conversion layer, and production method for wavelength conversion layer
WO2018128144A1
Curable composition containing quantum dots, cured material containing quantum dots, method for manufacturing optical member, and method for manufacturing display device
WO2018225782A1